Factors Affecting ICU Stay and Length of Stay in the ICU in Patients with HELLP Syndrome in a Tertiary Referral Hospital - Elif Ağaçayak; Rezan Bugday; Nurullah Peker; Ugur Deger; Gönül Ölmez Kavak; Mehmet Siddik Evsen; Talip Gul (International Journal of Hypertension)
Objective. The study aimed to compare patients with HELLP syndrome who require intensive care and who do not require intensive care and evaluate the factors affecting the length of stay in the intensive care unit. Methods. Patients were divided into two groups as follows: requiring intensive care (group 1) and not requiring intensive care (group 2). The data of both groups were compared in terms of demographic characteristics, transfusion amounts, length of stay in the intensive care unit, maternal complications, and mortality. Results. 14032 births in a tertiary center between 2011 and 2018 were evaluated in this study. During the study period, 342 patients were diagnosed with HELLP, and 32 (9.4%) of these were followed up in the intensive care unit. The length of stay in the intensive care unit was determined as 8.1 (7.2) days on average. Fresh frozen plasma, erythrocyte suspension, apheresis, and random thrombocyte transfusion were observed to be significantly more in group 1 patients. In the regression analysis, the most effective factor was found to be erythrocyte suspension and the length of stay in the intensive care unit was significantly longer in patients who had erythrocyte suspension transfusion. The receiver operating characteristic curve showed that the area under the curve value for erythrocyte transfusion was 70.6%. When the cutoff value of erythrocyte suspension was 450 (95% CI: 365–681) ml, the sensitivity was 43.8% and the specificity was 91.6%. Conclusion. We think that physicians should be careful that maternal morbidity and mortality may increase as the need for erythrocyte suspension transfusion increases in patients with HELLP syndrome. Minimum transfusion to hemodynamically stable patients can be more suitable in terms of morbidity and mortality in managing patients with HELLP syndrome requiring erythrocyte suspension transfusion. Precautions and measures should be taken in this regard.